Repertory grid: investigating personal constructs of novice programmers - Thota, Neena (Association for Computing Machinery, 2011)
In this paper, the repertory grid is presented as a technique to explore novice programmers' experiences within the context of an action research project. The theoretical and methodological aspects of the technique are discussed. The findings from the technique that combined quantitative and qualitative data analysis methods are provided. These findings relate to the learning process, learning content, and learning support as experienced by the students in an introductory object-oriented programming course. The repertory grid technique is then appraised for its relevance and usefulness to the project, and for its contribution to the diversity of computer science research methods. Insights gained from the use of the technique are shared with the community of computer science educators.
Keywords: mixed methods; novice programming; repertory grid

Macao: A Study on the Impact of Global, Regional and Local Forces. - Lampo, Alessandro; Care, Leanda (Signapore Management University, 2011)
Over the years Macao has been exposed to different cultures and has been influenced by various political and economic interests. The booming casino economy has ultimately transformed the city into the largest gambling hub in the world. In spite of the consensus about Macao's shiny future, there are factors (such as the large reliance on a single industry) and socio-economic problems (such as labor shortage, unequal income distribution, and inflationary pressure) that moderate the optimism. By making use of the Chatterjee and Nankervis' convergent and divergent process model for management, this paper examines how global, regional, and local forces have impacted the economic development process, form and type of organizations in Macao. The paper also suggests that the government implement a framework that develops and diversifies the economy but also takes into consideration the social needs of the community.

Evaluating an Enterprise Content Management for the Macao Government Agency - Pong, F.; Whitfield, R.; Negreiros, J. (Springer, 2011)
Information contained within documents is an essential ingredient of any office operation. A content management application (CMA) is an organization plan for the conception, use, retention, disposal and selective preservation of its data. Using an appropriate CMA framework can greatly help Macao Government agencies, for instance, that are increasingly using electronic means to create, exchange and store a major variety of records daily. By definition, a record is information, in whatever form, for government functions, activities, decisions and other important transactions. As expected, as the volume of electronic information increases, so does the complexity of managing electronic records. This project goal was to evaluate the software capabilities of the Alfresco© Enterprise Content Management (ECM) against a set of functional requirements, aimed by the Macao Government agency. Drawing on the results of this evaluation, the present analysis concludes that Alfresco© ECM is capable of supporting an entire agency needs related to the management of its records content.
Keywords: Alfresco©; Enterprise Content Management; Macao Government; Open Source Software